OPTIMIZATION OF MULTI-UNIT GAS TURBINE OPERATION FOR ELECTRICAL POWER GENERATION IN OIL AND GAS PRODUCTION FIELD - Rozieanshah, Rhobi
Oil and gas production field operation, requires electrical power to support its operations, both for the main needs for electricity supply for electrical submersible pump motors and platform utilities such as platform lighting, air compressor unit, production control room, and others. Gas turbines act as a prime mover which connected to an electric generator, is very important to provide electricity supply to the field. Gas conditioning facilities, such as gas compressor units are installed to boost pressure of natural gas supply as fuel specification requirement to the gas turbines. In this paper, will be explained the application of the gas turbine operation process and its supporting system for an oil production field in the Kepulauan Seribu, Indonesia. There are eleven Gas Turbine Generator (GTG) units operating in this field, and consist of two gas turbine models, namely Solar Taurus and Solar Mars. Difference between both models, is the design of the turbine engine system: single shaft (Taurus) and double shaft (Mars). And from its power generator output capacities. The GTG Solar Taurus unit operates at 4000 kW x 6 units and 4500 kW x 2 units, while the GTG Solar Mars unit operates at 9000 kW x 3 units. From the rating data for gas turbine units above, the maximum Power Plant capacity is around 60.0 MW (60.000 kW), with the average power consumption or load demand of the production field being around 40?50 MW (40,000?50,000 kW) in the last 10 years. There are three sources of natural gas fuel for GTG: raw associated gas (RAG), processed gas from the Banuwati platform (BWAG) and a mixture of both (BWAG + RAG). Each of these natural gas fuel sources has a different composition, which affects the specific gravity (SG), lower heating value (LHV) values, and Wobbe Index (WI). This thesis deals with the optimization of electric power generation from the eleven GTG units. As the company's objective is to optimize the use of natural gas fuel for GTG consumption due to its reserve limitation and save electrical energy used by Power Plant utility’s load (such as gas compressor units, gas cooler, and gas heater). The eleven GTG units have main differences in the power output capacity, the specifications of the gas fuel, compressor efficiency, gas producer turbine efficiency (on Taurus and Mars unit) and power turbine efficiency (on Mars unit only). The variable or parameter value affects the performance or thermal efficiency of each unit. From the diversity of the performance of the eleven units, an evaluation was carried out to optimize Power Plant operation by adjusting the GTG output power to achieve expected optimization, such as low gas fuel consumption, low use of electrical power in Power Plant utilities, high Power Plant thermal efficiency. To support this research study, Aspen HYSYS software version 14 is used as a tool in obtaining the expected optimization value. The optimization method used is SQP Hypotrech which is one of the options in the Optimizer feature of Aspen HYSYS.